2009
DOI: 10.1074/jbc.m803108200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Type 1 Is a Substrate for γ-Secretase-dependent Regulated Intramembrane Proteolysis

Abstract: Biochemical and genetic studies have revealed that the presenilins interact with several proteins and are involved in the regulated intramembrane proteolysis of numerous type 1 membrane proteins, thereby linking presenilins to a range of cellular processes. In this study, we report the characterization of a highly conserved tumor necrosis factor receptor-associated factor-6 (TRAF6) consensus-binding site within the hydrophilic loop domain of presenilin-1 (PS-1). In coimmunoprecipitation studies we indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 132 publications
2
38
0
Order By: Relevance
“…Through genetic knock-out of the presenilins, we have further demonstrated the essential role of the presenilins in ␥-secretase cleavage of TNFR1. Although it has been shown that ␥-secretase cleavage of the insulin-like growth factor 1 receptor, Notch, IL-1 receptor I, p75 NTR , or ErbB-4 receptor occurs in the presence of their corresponding ligands (40,50,58,(77)(78)(79), ligand-induced cleavage has not been shown for other receptors, such as the growth hormone receptor. Here we demonstrate that TNF␣ stimulation can induce ectodomain shedding, generation of TNFR1 CTF, and subsequent ␥-secretase cleavage of TNFR1, perhaps pointing to a general mechanism of ligand-mediated regulated intramembrane proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Through genetic knock-out of the presenilins, we have further demonstrated the essential role of the presenilins in ␥-secretase cleavage of TNFR1. Although it has been shown that ␥-secretase cleavage of the insulin-like growth factor 1 receptor, Notch, IL-1 receptor I, p75 NTR , or ErbB-4 receptor occurs in the presence of their corresponding ligands (40,50,58,(77)(78)(79), ligand-induced cleavage has not been shown for other receptors, such as the growth hormone receptor. Here we demonstrate that TNF␣ stimulation can induce ectodomain shedding, generation of TNFR1 CTF, and subsequent ␥-secretase cleavage of TNFR1, perhaps pointing to a general mechanism of ligand-mediated regulated intramembrane proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids, Site-directed Mutagenesis, and TransfectionspcDNA3.1-PS1 was generated in-house as described previously (40). The pBABE-TNFR1 (human) expression plasmid was a gift from Dr. Martin S. Kluger (Yale University School of Medicine).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined mode of action of ␣-and ␥-secretases is reminiscent of the sequential protease involvement in processing of substrates of the ␥-secretase, such as the amyloid precursor protein (29,30). Besides amyloid precursor protein, secretases have been reported to play a role in cleaving and processing a variety of different proteins, including MHC class I proteins, in particular human leukocyte antigen A2 (31), the interleukin-1 receptor type 1 (IL-1R1) (32), leukosialin/ CD43 (33), transmembrane-associated chemokines, the Notch receptor, and others (34). These processes probably occur close to the cellular membrane through juxtamembranous cleavage events as demonstrated previously for CD43 (33).…”
Section: Discussionmentioning
confidence: 99%